A correction method for HVDC transmission plan considering the correlation between sending end new energy generation and receiving end loads. (July 2018) - Lei, Liang; Julong, Wang; Mingying, Li; Ming, Chen
Abstract: Recently, new energy is conversely distributed and centralized grid connection which need transmit redundant power to other regions urgently by HVDC system. Based on the characteristics of new energy, this paper analyzes the correlation between sending end new energy and receiving end loads by person correlation coefficient method and proposes a correction method for HVDC transmission plan considering the correlation which promotes new energy penetration level and improves utilization of HVDC system. By taking a HVDC system as an example, the results of analyzing practical scheduling data in 2015 demonstrate the feasibility of the proposed method.